TBTs, Firm Organization and Labour Structure - The Effect of Technical Barriers to Trade on Skills - Giorgio Barba Navaretti; Lionel Fontagné; Gianluca Orefice; Giovanni Pica; Anna Cecilia Rosso (Center for Economic Studies and ifo Institute (CESifo), 2019)
Trade shocks in export markets may affect the employment composition and the organization of exporting firms. In particular, the imposition of new technological standards in destination markets may force exporters to adjust the firm's organization to comply and cope with the additional complexity of the new production process. This paper investigates the effects on firms' organization of shocks induced by the introduction of Technical Barriers to Trade (TBTs) in exporting countries. It relies on the Specific Trade Concern (STC) data released by the WTO to identify trade-restrictive TBT measures, combined with matched employer-employee data for the population of French exporters over the period 1995-2010. It also exploits information on the list of product-destinations served by each French exporter. Controlling for tariffs and for a given state of technology in the sector of the firm, it finds that exporters respond to increased complexity associated with restrictive Technical Barriers to Trade at destination by raising the share of managers at the expense of blue collars, white collars and professionals. This paper is related to the growing literature exploring how firms organize production in hierarchies to economize on their use of knowledge. It is also related to the well beaten literature on the labour market effects of trade, but from the perspective of exports rather than imports.
Keywords: F13; F16; J82; 330; skill composition; labor demand; job polarization; trade barriers